If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -21x + -90 = 0 Reorder the terms: -90 + x + -21x = 0 Combine like terms: x + -21x = -20x -90 + -20x = 0 Solving -90 + -20x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '90' to each side of the equation. -90 + 90 + -20x = 0 + 90 Combine like terms: -90 + 90 = 0 0 + -20x = 0 + 90 -20x = 0 + 90 Combine like terms: 0 + 90 = 90 -20x = 90 Divide each side by '-20'. x = -4.5 Simplifying x = -4.5
| 3(2x-1)=3x+6 | | x(12-2x)(10-2x)=0 | | y/4-3=y/3 | | 3n+2=-40 | | -3-20=-x+10 | | x+y=365 | | 6x+4=9x-17 | | 10x-3y+3x-4y=0 | | 3x-2=-47 | | 21(w-937)=630 | | 0=8+4x | | 7x-11=x+1 | | -47+5x=30-2x | | k-10/2=5 | | w-650=500000 | | 2.33*x=9 | | 4.8+v=14 | | (4z-7)(6+z)=0 | | x(32-6x)=0 | | (4z-7)(5+z)=0 | | x-32=-5(6x-6) | | 9(-4-p)=3(-4p-8) | | k-8=24 | | 4/17y-16=0 | | ax^2+bs+c=0 | | 7/4=9/r | | 6[5(3-9)-1]+2= | | 7x-2=5x-9 | | f(12)=.25(12-3) | | 8x-1=11x-9 | | 2-u=6 | | -5(1+6X)-8x=38+5x |